New Environmental Protection Taxes in China from the Perspective of Environmental Economics - Qianyang Tu; Ying Wang (Discrete Dynamics in Nature and Society)
In recent decades, most countries have implemented environmental protection by formulating relevant environmental regulations to reduce environmental pollution and improve environmental quality. China enacted new Environmental Protection Tax Law in 2018 and abolished the old system of pollution discharge fees. This paper analyzes and predicts the effectiveness of these new environmental tax policies within the framework of a macroeconometric dynamic stochastic general equilibrium (DSGE) model. Bayesian estimation is applied to estimate dynamic parameters based on China’s macroeconomic data from 1978 to 2018. We find that the implementation of China’s new environmental tax will lead to a significant increase in environmental quality through a reduction in the amount of pollution. However, the study reveals that new environmental taxes may have certain negative influences on economic growth. Consumption, output, wages, and capital could fall by 1.26%, 0.34%, 1.16%, and 1.12%, respectively, which may slow the pace of China’s development.